EFEKTIVITAS GREENHOUSE DALAM MENINGKATKAN PRODUKSI TOMAT MOMOTARO: STUDI KASUS PADA KELOMPOK TANI JAYA LESTARI - Ratnakaniya, Nadira Marsandri; Br Sebayang, Veralianta (Institute of Computer Science (IOCS), 2025)
This research aims to understand the effectiveness of adding a simple greenhouse made of bamboo in increasing the production capacity of momotaro tomatoes in the Jaya Lestari Farmers Group and describe the business development process from financial and non-financial aspects. The market demand for momotaro tomatoes shows that demand is increasing, while the production capacity of farmer groups is still limited and has not been able to meet demand efficiently. The results of the study were evidenced by the t-test values of paired samples showing a significant increase in production of p-values smaller than 0.05. The analysis of NPV financial feasibility is IDR 304,525,316, internal rate of return (IRR) is 56.79%, Net B/C is 3.34, and Gross B/C is 1.67, and payback period of two years and three months of return, which shows that this business is successful to run. The results of the sensitivity analysis show that the business is relatively stable to input costs, but sensitive to production failures. The application of greenhouses has proven to be effective in increasing production and is feasible for businesses to run. However, a managerial strategy is needed to ensure production stability so that business operations remain stable to increase production and profitability so that business operations remain stable.